DYNAMIC MODELING AND SIMULATION ON DRY REFORMING OF METHANE OVER FIXED-BED REACTOR TO PRODUCE SYNTHESIS GAS - Rashid Bin Abdul Razak, Abdur
Interest in dry reforming of methane (DRM) is driven by the need to utilise carbon dioxide contained in natural gas. The catalytic reaction of carbon dioxide with methane under a specified condition will generate synthesis gas. This product with a ratio of hydrogen to carbon monoxide near two is suitable for producing dimethyl ether, acetic acid, and alcohol via oxo-alcohol synthesis. However, dry reforming of methane is a reversible and endothermic reaction, which requires a large amount of energy. In addition, DRM requires high operating temperatures to achieve maximum equilibrium conversion. Therefore, an investigation on the effect of the dynamic operation on the catalyst’s activity during the DRM was studied in this paper. In this study, an isothermal one-dimensional pseudo-homogeneous reactor model was developed and validated. A Langmuir Hinshelwood kinetic model from reference literature was used to complement the model. The model was simulated with the help of FlexPDE Professional Version 6.51 software. The reactor model was simulated under the steady-state and unsteady-state. Results from the steadystate simulation were used as a base case and compared with the unsteady-state simulation. In steady-state conditions, the CH4 and CO2 conversions obtained from the numerical simulation are 71.72% and 82.47%, respectively, with H2 and CO yield equals 1.325 and 1.540. Feed modulation and regular feed admittance were introduced for unsteady-state simulation. Several variations of the feed modulation with switching time (ST) between 0.05 and 4.00 s and concentration amplitude (?) between 1.25 and 1.75 was simulated. At feed ratio of CH4:CO2 1:1, CH4 feed modulation at ST 0.25 s and ? 1.5 surpassed the CO2 steady-state conversion to 83.24% , H2 yield to 1.348, CO yield to 1.559. CH4 conversion during steady state for feed ratio CH4:CO2 1:2, exhibited a significant increase of CH4 conversion to 91.33%, however decreasing the CO2 conversion to 63.20% and H2/CO ratio to 0.68. CH4 feed modulation for feed ratio CH4:CO2 1:2 does not show any significant change in response variable compared to its steady state conditions. The CO2 feed modulation increased the CH4 conversion to 72% and H2 yield to 1.571. Regular feed admittance of H2O with tc between 0.2 and 2 s at constant ? 1 were simulated. It showed at tc 0.2 s, the CH4 conversion increased to 75.51%, and H2/CO ratio to 1.011. However, the CO2 conversion decreased to 76.38%. Introduction of 100% N2 with tc 2 s and ? 3.0 increases the CH4 and CO2 conversion slightly to 72.86 and ii 83.44%, respectively. Regular intermittent H2O with tc 2 s and ? 3.0 increase the CH4 conversion to 76.53% while decreasing the CO2 conversion to 69.27%. In addition, the H2/CO ratio is increased to 1.10.